CHANGES IN HAEMATOLOGICAL AND BIOCHEMICAL PARAMETERS IN RAM LAMBS FED ON HORSE GRAM TANNINS AND PROBIOTIC SUPPLEMENTATION DIETS (Indian Journal of Animal Production and Management, 2016)
An experiment was conducted to study the effect of probiotics supplementation and tanniferous diet  inclusion on health status by estimating the hematological and biochemical diagnostic parameters in  Deccani ram lambs. 18 Deccani ram lambs of uniform body weight (16.5±0.64 kg) were randomly allotted  to 3 groups in a completely randomized design. The dietary treatments were viz., T1: Basal diet (chopped  sorgum stover + chopped green fodder as roughage source) + group 1 concentrate, T2: Basal Diet + Group  2 concentrate (with horse gram), T3: Basal diet + Group 3 concentrate supplemented with probiotics @  4kg per100kg concentrate. Deccani ram lambs were fed the respective diets ad lib. to meet the nutrient  requirements throughout 90 days of feeding trial. Blood glucose concentration was comparable among the  experimental groups, however relatively higher (P
Keywords: Horse gram; Probiotic; Serum biochemical parameters; Tannins